2017
DOI: 10.1016/j.biortech.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extended famine conditions on aerobic granular sludge stability in the treatment of brewery wastewater

Abstract: Results obtained from three aerobic granular sludge reactors treating brewery wastewater are presented. Reactors were operated for 60d days in each of the two periods under different cycle duration: (Period I) short 6h cycle, and (Period II) long 12h cycle. Organic loading rates (OLR) varying from 0.7kgCODmd to 4.1kgCODmd were tested. During Period I, granules successfully developed in all reactors, however, results revealed that the feast and famine periods were not balanced and the granular structure deterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 32 publications
1
43
1
3
Order By: Relevance
“…The removal rate of the polarized system was maintained at 80.3–81.8%, significantly higher than that of the open‐circuit system (74.6–75.9%; p <.05). The anaerobic treatment of brewery wastewater could remove less than 75% of the COD, while a bioelectrochemical treatment can provide a COD removal rate higher than 80% (Corsino et al, 2017; Tejedor‐Sanz et al, 2018). The results of this and previous studies suggest that the electrode polarization considerably contributed to the removal of organic matter from brewery wastewater.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The removal rate of the polarized system was maintained at 80.3–81.8%, significantly higher than that of the open‐circuit system (74.6–75.9%; p <.05). The anaerobic treatment of brewery wastewater could remove less than 75% of the COD, while a bioelectrochemical treatment can provide a COD removal rate higher than 80% (Corsino et al, 2017; Tejedor‐Sanz et al, 2018). The results of this and previous studies suggest that the electrode polarization considerably contributed to the removal of organic matter from brewery wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…Wastewater often contains various suspended inorganic and organic particulates. It is likely that these particulates from brewery wastewater were trapped during the biofilm development (Corsino et al, 2017; Khalfbadam, Ginige, Sarukkalige, Kayaalp, & Cheng, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In the actual treatment process, biogas production and removal of residual pollutants are usually produced in combination with anaerobic and aerobic processes. AGS can be successfully cultured when dealing with actual brewery wastewater (Corsino et. al.…”
Section: Anaerobic Granular Sludgementioning
confidence: 99%
“…However, the understanding on the capacity of the system to recover the granulation process when instability occurs remained scarce since current research works on continuous variation in the OLR applied have been rarely reported [10]. Most of the works regarding stability as presented in Table S1 have been performed using synthetic wastewater with constant OLR except for Corsino et al [11] and Liu and Tay [12] which used brewery and industrial wastewater, respectively.…”
mentioning
confidence: 99%